Fusarium Wilt of Cucumber- A Review - Sharma, Deepika; Shukla, Arti (International Journal of Economic Plants, 2021)
Cucumber (Cucumis sativus L.) wilt is an important disease caused by Fusarium oxysporum. The disease is prevalent in most of the countries of the world with yield losses ranging from 40–70%. Characteristic symptoms of the disease include pre and post-emergence damping-off, stunting, chlorosis, necrosis and finally wilting of the older leaves with brown vascular discoloration. Two formae speciales of F. oxysporum have been described in cucumber. The fungus grows profusely on the culture media and produces macroconidia which are tapered with a slight hook, microconidia oval in shape and terminal or intercalary chlamydospores. The disease prevails under the conditions having abundant soil moisture and soil temperature ranging from 24–27oC and no growth of the fungus was observed above 37oC. The pathogen is host-specific to cucumber with muskmelon and watermelon being slightly sensitive. Due to environment and health concerns associated with large scale use of chemicals, the application of resistant germplasm, bio-control agents, and bio formulations is more reliable. This review describes the use of resistant germplasm, bio-control agents, bio-formulations and fungicides to control Fusarium wilt of cucumber.